Pricing currency option in a mixed fractional Brownian motion with jumps environment - Shokrollahi, Foad; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
A new framework for pricing the European currency option is developed in the case where the spot exchange rate fellows a mixed fractional Brownian motion with jumps. The jump mixed fractional partial differential equation is obtained. Some Greeks and properties volatility are discussed. Finally the numerical simulations illustrate that our model is flexible and easy to implement.